(untitled) (LACCEI, 2024)
The research presents a methodology where the application of the Chinese postman problem, which is based on the theory of weighted Eulerian graphs, and the problem of coverage of sets of binary integer linear program was combined, as an alternative to model non-Eulerian routes, with the aim of optimizing the design of the urban solid waste collection routes, of the municipality of the district of Cajamarca, located in the province and department of the same name in Peru. The scope of both problems allowed to generate an alternative that facilitated the optimal design of these routes, which in practice is very complex due to the range of variables that affect this process, such as the increase in population density and the volume of waste generation, urban planning, the capacity of available resources, among others, managing to reduce the total average travel distance per route by 66.6%, which demonstrates the need to be flexible when modeling the routes, generating the necessary adaptations of the technical aspects to meet the particularities of reality.